A arte literária de Eliane Potiguara, Márcia Waina Kambeba e Ehuana Yaira Yanomami : cosmo-histórias indígenas espiralando no tempo - Zattoni, Andreia Marcia (2024)
The Indigenous Women’s History told by their literary and artistic works is the object of this thesis. Indigenous Literature and Art are part of a Movement that, although diffuse, has common principles, such as the dissemination of indigenous ways of life, their cosmologies and perceptions of the world. Thus, it constitutes an identity, critical and disruptive resistance movement. The works of Eliane Potiguara, Márcia Waina Kambeba and Ehuana Yaira Yanomami are inserted in the context of this Movement and with these authors the arguments of this thesis are built, supported by indigenous research and writing methodologies. The thesis presented is that the specificities of indigenous literature configure it as a privileged instrument for the recording of indigenous histories because they express indigenous epistemologies, cosmoperceptions and cosmologies in a more appropriate way. In the work of these women, the narratives are being constructed in a spiral time, which seeks in ancestry the necessary understandings for their identity constructions and the affirmation of their resistances. They also welcome indigenous cosmologies with their perceptive, sensitive, and creative meanings, typical of oral tradition, as a Cosmohistory. Spiral time and Cosmohistory are concepts developed, respectively, by Leda Maria Martins and Federico Navarrete Linares and used here to identify historical narratives with multiple ancestral experiences and affective complicities. Based on the authors' spiral Cosmo-histories, it is proposed to conceive indigenous literature and art as documents of historical record. This, not only because they store information, but because they are instruments that best translate Indigenous Women’s History.